Ali Fuat Başgil (1893-1967): a principled pragmatist - Islam, Arshad (Ondokuz Mayis University, Carsamba, Samsun, Turkey, 2017)
This study examines Ali Fuat Başgil’s intellectual vigour as a jurist, his leadership capability as a practical politician, and his insights on political leadership as a statesman and philosopher. Başgil was one of the key intellectual figures during and after the Democrat Party government, and the Justice Party honoured his thoughts, ideas and actions. Başgil’s talent was spotted early and he was invited to Ankara from the world of university politics in Istanbul by the Prime Minister Adnan Menderes (1899-1961). He was a man of principle and always supported justice and truth, which made him immune to the power intrigues that undermined Turkey at various junctures. After the military coup of May 27, 1960, Başgil was one of the candidates for the presidency but he was forced to withdraw his name and renounce his candidacy on pain of execution by the representatives of the junta, who had just executed Menderes. Due to his genuine belief in democracy and his apprehension of the dangers ahead under military dictatorship, he refused to be a token president of the Senate when the military attempted to exploit the popular esteem in which he was held, and he courageously resigned from the phoney representative system. Başgil felt that courage was the fundamentally important quality for politicians, enabling them to make effective and appropriate decisions in times of crisis. This study seeks to determine political environment during and after 1960s military coup to highlight Başgil’s role and address a number of key political challenges in which he lived.